2022
DOI: 10.3390/su14052824
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Communication in the B2C Market—The Impact of Packaging

Abstract: The purpose of this study was to widen the knowledge about the recycling behaviour of consumers in order to understand their motivations related to the separate collection of household waste. This work encompasses a segmentation analysis revealing discrepancies between the respondents, who were profiled into three clusters: Engaged in green, characterised by high values of pro-environmental attitudes; Indolent adopters, described by respondents revealing moderate attitudes towards sorting waste; and Ecological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
(34 reference statements)
0
0
0
Order By: Relevance
“…While the studies add to the empirical information and to the understanding of issues from various theoretical viewpoints, they remain difficult to unify and cross-compare [206]. Similar research into sustainable packaging [207][208][209][210][211][212][213][214][215][216][217][218][219][220][221][222] also considers a variety of countries using a variety of models and several factors. Even for green purchase behavior in general, there is still a need for continued research to investigate the applicability and usability of various marketing and management theories, and significantly more effort needs to be directed towards identifying green customer segments based on demographic, psychographic, and behavioral characteristics, especially using techniques such as data mining and artificial intelligence [223].Circular behaviors represent a range of activities, including recycling and reusing goods; acquiring certified green products or recycled, remanufactured, or reconditioned products; refilling products; product care and maintenance; waste separation; returning products at their end of life; sharing products and services; reducing consumption; and local and organic consumption, with political, economic, environmental, and demographic factors influencing such behaviors [224].…”
Section: Consumer Behaviormentioning
confidence: 99%
“…While the studies add to the empirical information and to the understanding of issues from various theoretical viewpoints, they remain difficult to unify and cross-compare [206]. Similar research into sustainable packaging [207][208][209][210][211][212][213][214][215][216][217][218][219][220][221][222] also considers a variety of countries using a variety of models and several factors. Even for green purchase behavior in general, there is still a need for continued research to investigate the applicability and usability of various marketing and management theories, and significantly more effort needs to be directed towards identifying green customer segments based on demographic, psychographic, and behavioral characteristics, especially using techniques such as data mining and artificial intelligence [223].Circular behaviors represent a range of activities, including recycling and reusing goods; acquiring certified green products or recycled, remanufactured, or reconditioned products; refilling products; product care and maintenance; waste separation; returning products at their end of life; sharing products and services; reducing consumption; and local and organic consumption, with political, economic, environmental, and demographic factors influencing such behaviors [224].…”
Section: Consumer Behaviormentioning
confidence: 99%
“…Previous studies reported how the sorting behavior is an unconscious process determined by habits [22]. Among the theories developed and addressed in former literature concerning consumers' behavior, it is possible to recall the Theory of Reasoned Actions (TRA) and the Theory of Planned Behavior (TPB) [23][24][25][26]. The TRA and the TPB are closely linked, with the TPB being a conceptual extension of the TRA.…”
Section: Introductionmentioning
confidence: 99%